Optimization design of international talent training model based on big data system - Wang, Jing (Frontiers in Psychology, 2022)
With the deepening of the concept of "global village", the exchanges between countries in the world are deepening. This has led to ever-closer ties between countries and regions. They are more and more interdependent and mutually restrictive. Internationalization has become an inevitable trend and trend in the development of higher education in the process of globalization. Developed countries have developed earlier in the field of education internationalization and have more mature experience, which provides a reference for the development of other countries. This paper aims to study the optimization design of the international talent training model based on the big data system. In this paper, the system analysis method is used for theoretical discussion. It establishes an index system of graduate students' international talent training mode through AHP, and puts forward a breakthrough for international education in colleges and universities. This paper believes that market enterprises should improve the human resource management platform, strengthen the promotion of corporate culture in colleges and universities, and take multiple measures to support the effective implementation of school-enterprise cooperation. This paper deeply studies the current situation of the international talent training model in colleges and universities, and finds out the deficiencies in the international talent training model. It also optimizes the path for the cultivation and development of international talents, which provides a basis for regional development and cultivation of international talents. The experimental results of this paper show that 20.1% of students believe that international education is to adapt to educational development, 25.4% of students believe that it is mainly to meet the needs of student development, and 62.2% of students believe that college majors lack internationalization characteristics.